The Role of Local Religious Figures (Kiai) in Strengthening Political Participation in Post-new Order Madura 1998-2019 - Topan, Ali; Hakim, Abdul (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2023)
This research aims to conduct an in-depth study of the role and existence of local Madurese religious figures in strengthening political participation in Madura. The local religious figures referred to are kyai, who are known to have a significant role and influence in Madura. The method used in this research is the historical method which includes four steps, namely: heuristics, source criticism, interpretation, and historiography. The results of this research show that kiai in Madura have a significant role and influence in strengthening community participation in general elections, both at the regional and presidential elections. The role and influence of the kyai are obtained because the Madurese people are known to have respect and obedience towards the kyai. In the context of Madurese society, kyai are people who have strong religious knowledge, so when Madurese chooses leaders, they tend to use the kyai's political attitudes and choices as role models or political references. Penelitian ini bertujuan melakukan kajian mendalam terhadap peran dan eksistensi tokoh agama lokal Madura dalam memperkuat partisipasi politik di Madura. Tokoh agama lokal dimaksud adalah kalangan kyai, yang selama ini dikenal memiliki peran dan pengaruh signifikan di Madura. Adapun metode yang digunakan dalam penelitian ini adalah metode sejarah yang di dalamnya mencakup empat langkah, yakni: heuristik, kritik sumber, interpretasi, dan historiografi. Hasil penelitian ini menunjukkan bahwa kiai di Madura memiliki peran dan pengaruh signifikan memperkuat partisipasi masyarakat terhadap pemilihan umum, baik pemilihan di level Pilkada maupun Pilpres. Peran dan pengaruh kyai tersebut diperoleh karena masyarakat Madura dikenal mempunyai sikap hormat dan patuh terhadap kyai. Dalam koteks masyarakat Madura, kyai adalah orang yang memiliki ilmu agama yang mumpuni, ketika orang Madura memilih pemimpin, maka mereka cenderung menjadikan sikap dan pilihan politik para kyai sebagai panutan atau referensi politik.